Comparison of the Indonesian and South Korea Impeachment System as a Method of Power Limitation - Sibuea, Hotma P. (Budapest International Research and Critics University, 2021)
Abuse of power is a classic universal phenomenon since the time of Ancient Greece. Humanity has developed various methods of controlling and limiting power systems since ancient times. Each country forms and develops methods and systems for limiting (supervising) power with various characteristics according to the needs, aims, objectives, value systems, philosophy, history, and natural environment of each nation. Several systems of control and limitation of power have been developed by mankind, such as the theory of separation of powers, the theory of checks and balances, the judicial review system, and others. All systems and methods of limiting and supervising power are aimed at preventing abuse of authority that results in violations of human rights and the rights of citizens. One of the systems of control and limitation of power developed by mankind is impeachment. The system and methods of impeachment are well known in various systems of government. Impeachment is a method of limiting the power of public officials. With impeachment, public officials can be dismissed during their term of office. In this paper, the impeachment methods and systems that are discussed and compared are the Indonesian impeachment model with a presidential system and South Korea's impeachment model with a parliamentary system. The legal issues (issues) under study relate to the similarities and differences in the methods and systems of impeachment in the two countries. The research method used is the juridical-normative research method. In a conclusion, the research is the Indonesian and South Korean impeachment systems and methods have significant similarities and differences within the framework of different government systems. Amendments to the 1945 Constitution need to be made as a change to a better method and system of impeachment.